Teaching Young Learners’ Listening Skills with Advantageous Activities - Ismatova Fayyoza Mashrab Qizi (Zien Journals, 2022)
This research deals with advantageous activities for teaching listening skill of young learners. “Young learners” includes ages from 7 to 12 years old and if they are under 7 years old are named “Very young learners”. So this article surely helps teachers who are teaching ages from 5 to 12 years old. The article provides variety of practical advises and activities based on listening skill of children for teaching young learners.
Keywords: Listen and do; Put up your hand; Mime stories; activities